Static seismic reliability analysis of SSTF structures - ICASP14; Lu, Zhaohui; Zhang, Xuanyi; Zhao, Yangang; Liu, Huijuan (My University, 2023)
In order to evaluate the seismic performance of the steel staggered truss framing (SSTF) structural system, the seismic reliability analysis of the structure is carried out in this paper. The limit state function of SSTF structural load bearing capacity was established by taking the total horizontal seismic action at the bottom of the structure reaching the ultimate base shear as the limit state. With the same amount of steel used as the basis, the SSTF structural analysis models were established for the common steel frame structure and six different truss arrangement forms. The failure probabilities of the common steel frame structure model and SSTF structure model under different seismic intensities were calculated using the high-order moment method, and the corresponding failure probability curves were drawn. The results show that: Most of the SSTF structural models have better seismic performance than the common steel frame structural models; Increasing the number of additional members in the truss helps to improve the seismic performance of the SSTF structure; The form of connection between vertical web and chord of the truss affects the seismic performance of the SSTF structure, and the rigid connection is more beneficial than the hinged connection to improve the seismic performance of the SSTF structure.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED